Probiotic potential of Enterococcus faecalis strains isolated from meconium - Al Atya, Ahmed K.; Drider-Hadiouche, Karima; Ravallec, Rozenn; Silvain, Amadine; Vachee, Anne; Drider, Djamel (Frontiers in Microbiology, 2015)
107 bacterial isolates with Gram positive staining and negative catalase activity, presumably assumed as LAB, were isolated from samples of meconium of six donors at Roubaix hospital, in the north of France. All these bacterial isolates were identified by MALDI-TOF mass spectrometry as Enterococcus faecalis. However, only six isolates among which E. faecalis 14, E. faecalis 28, E. faecalis 90, E. faecalis 97 and E. faecalis 101 (obtained from donor 3) and E. faecalis 93 (obtained from donor 5) were active against some Gram negative bacteria (GNB) and Gram positive bacteria (GPB), through production of lactic acid and bacteriocin like inhibitory substances (BLIS). The identification of these isolates was confirmed by 16rDNA sequencing and their genetic relatedness was established by REP-PCR and pulsed field gel electrophoresis (PFGE) methods. Importantly, the aforementioned antagonistic isolates were sensitive to various classes of antibiotics tested, exhibited high scores of coaggregation and hydrophobicity, and were not hemolytic. Taken together, these properties render these strains as potential candidates for probiotic applications.